The Effect Of Dictogloss Technique On Improving Students Writing Skill Of Descriptive Text At The Tenth Grade Students Of SMK Muhammadiyah Kudus - Ahmad Nur Syafiq; Amalia Rahmawati; Anawari Anwari; Tyas O ktaviana (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The aim of this study is to examine the effect of dictogloss techniqueon improving the writing ability of students on descriptive text attenth grade students of SMK Muhammadiyah Kudus in the academicyear of 2019/2020. This study was classroom action research usingmodel of Kemmis dan McTaggart containing reconnaissance,planning, action dan observation and reflextion conducted in twocycles. The total samples of this study were all students of tenthgrade of SMK Muhammadiyah Kudus consisting of 70 students.Later on, the data were collected through observation, interview andtests using interview guidlines, observation sheet and English writingrubric and then analyzed using descriptive analysis. This studyshowed that the use of dictogloss technique was able to improvewriting skill of descriptive text for students. It can be seen from thedifferent means from pre test and post test in the way that mean scoreof pre test was 8, in the cycle one was 9.5, in the cycle two was11.63, and in the post test was 14,5. Furthermore, based on theapplication of its technique the students were able to generate theiridea to produce well organized descriptive texts. They were also ableto use the appropiate vocabulary, grammar, punctuation, spelling andcapitalization in the writing. During the teaching and learning processthey also showed positive responses towards the lesson,enthusiastically joined the teaching and learning activities and did thetask well.